Couple Resilience to Economic Pressure Over Time and Across Generations. Issue 2 (5th February 2016) - Masarik, April S.; Martin, Monica J.; Ferrer, Emilio; Lorenz, Frederick O.; Conger, Katherine J.; Conger, Rand D.
Abstract : Research suggests that economic stress disrupts perceived romantic relationship quality, yet less is known regarding the direct influence of economic stress on negative behavioral exchanges between partners over time. Another intriguing question concerns the degree to which effective problem solving might protect against this hypothesized association. To address these issues, the authors studied two generations of couples who were assessed approximately 13 years apart (Generation 1: N = 367, Generation 2: N = 311). On average and for both generations, economic pressure predicted relative increases in couples' hostile, contemptuous, and angry behaviors; however, couples who were highly effective problem solvers experienced no increases in these behaviors in response to economic pressure. Less effective problem solvers experienced the steepest increases in hostile behaviors in response to economic pressure. Because these predictive pathways were replicated in both generations of couples, it appears that these stress and resilience processes unfold over time and across generations.